Penerapan Diferensial untuk Mengukur Laju Perubahan Volume Air Galon - Muhammad Minan Chusni; Khoirun Nisa; Muhammad Haidir; Rismaya Fitriyani (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2018)
The aim of this research is to apply Torricelli law in order to determine flow velocity of fluid by calculating the rate of change of gallon bottled water volume by using the derived equation and measuring the time required until the water in the gallon is exhausted. This research used experimental method by varying the height of liquid in gallons so that the variation of fluid velocity and the rate of volume change are obtained. The results show that the maximum fluid velocity was 0.22 m/s with a rate of change of volume of 0,010 m3/s, and the minimum fluid velocity of 0.063 m/s with a rate of change in volume of 0,0028 m3/s.